Unemployment an unauthorized unique road about apathy and poverty the Macedonian man without knowledge and skills - Ljupco, Naumovski; Jasminka, Naumovska (International research journal of management, IT and social sciences, 2017)
The topic was aimed at debating the reality that Macedonia as a welfare state and unemployment, ie poverty, constitutional freedom and the right to seek or work to protect from poverty. The aim was the different directions to the concepts of anomalies: unemployment, apathy, poverty, and knowledge related to the concept - Macedonian social state. The topic of socialization was relevant not only for Macedonia but also for all countries in the world now that we are in transition and transformation, dynamism and complexity of the activity of social processes. Macedonian current conditions have changed for the social order of the lost values of the previous rules by taking risks because they are inevitable and more complex. It is the beginning to its characteristics representing qualitative changes in morality, which has not led to turbulence. The lack of value, but also the normative solidarity of social existence, did not lead to a situation of threatening the state of the complex - integrity and autonomy.